Decannulation and improvement of responsiveness in patients with disorders of consciousness. Issue 4 (21st April 2022) - Hakiki, Bahia; Pancani, Silvia; Draghi, Francesca; Portaccio, Emilio; Tofani, Ariela; Binazzi, Barbara; Anna Maria, Romoli; Scarpino, Maenia; Macchi, Claudio; Cecchi, Francesca
ABSTRACT: Decannulation is a rehabilitation milestone in patients with Disorders of Consciousness (DoC). investigate the relationship between decannulation and improvement of responsiveness (IR) in DoC. 236 tracheostomized patients with severe Acquired Brain Injury and DoC admitted in the Intensive Rehabilitation Unit were retrospectively included. They received personalized interdisciplinary rehabilitation. At discharge, IR was evaluated. The association between IR and demographic/clinical data was investigated using a logistic regression analysis, both in the Unresponsive Wakefulness Syndrome (UWS) and Minimal Consciousness State (MCS) group, divided according to their Coma Recovery Scale-Revised score at admission. In the UWS group ( N = 107), only decannulation was associated with IR at discharge (OR: 5.94, CI: 2.08–16.91, p = .001). In the MCS group ( N = 129) time post-injury (OR: 0.983, CI: 0.97–0.99, p = .012) and decannulation were associated with IR at discharge (OR: 17.9, CI: 6.39–50.13, p < .001). Decannulation and IR were found to be strongly related, independently from the initial clinical state. While the retrospective nature of the study could not exclude that decannulation may be a consequence of a spontaneous recovery, the obtained results may disclose its potential influence on the clinical history of patients with DoC.